The singing geese - Wahl, Jan.; Brown, Sterling (New York : Lodestar Books, 1998)
Sam Bombel shoots a goose and brings it home for his wife to cook for dinner, but when it is set on the table, the other geese come to reclaim it.
Keywords: African Americans; Folklore -- Maryland; Tall tales